Comparison of the Efficacy of Rupatadine with Levocetirizine in Patients with Persistent Allergic Rhinitis - Hanprasertpong, Nutthiya; Warinruk, Jariyakul; Fooanant, Supranee; Rojanasthein, Noppamas; Roongapinun, Sukit; Arpornchayanon, Warangkana; Manorot, Maleeya (Journal of Basic and Applied Pharmacology, 2016)
Allergic rhinitis is a global health problem of increasing prevalence. Its bothersome symptoms can disturb sleeping patterns and impact on daily activities. A prospective, randomized, single-blind, active controlled study was performed to compare the clinical efficacy, particularly on the nasal obstruction of rupatadine 10 mg (RUP) with levocetirizine 5 mg in the treatment of persistent allergic rhinitis (PER) for 4 weeks. The clinical assessments included the total nasal symptom score (TNSS), total ocular symptom score (TOSS), nasal peak inspiratory flow (PNIF), nasal cytology as well as the percentage of the responders who exhibiting the TNSS declined by 50% or more. After 4 weeks of treatment, TNSS and TOSS of both groups were significantly improved with no difference between groups. Percentages of the responders were 50% and 57.3% in LEV and RUP group, respectively. Only the PNIF of LEV group significantly improved from baseline value. There was no significant change in inflammatory cells when compared with the baseline data of nasal cytology. The mean changes in PNIF and nasal inflammatory cells did not differ between both treatment groups. Although RUP group seemed to use the rescue treatment less than LEV group but no significant difference was found. The most common adverse events were somnolence and drowsiness with similar frequency in both groups. In conclusion, RUP 10 mg provides effective control of allergic symptoms, including nasal obstruction comparable to LEV 5 mg in PER patients.